Development and validation of the acculturative stress among Iranian diaspora scale - Dokoushkani, Farimah; Juhari, Rumaya; Abdollahi, Abbas; Motevaliyan, Seyed Mehdi; Villanueva, Randle Aaron; Zhuo, Job Chen (Michigan State University, 2019)
The current study’s aims were to develop and validate a measure of acculturative stress among Iranian diaspora population. The instrument of 27 items was administered to a total of 610 Iranian students studying in Malaysian universities. Exploratory and confirmatory factor analyses offered evidence for a reliable and valid six-factor construct that assess a range of stresses for Iranian diaspora: 1) Concern about finances and a desire to stay in any country except Iran (CF); Language difficulties (LD); 3) Interpersonal stress (IS); 4) Stress from new culture and desire to return to Iran (SNC); 5) Academic pressure (AP); and 6) Stress from new rules and regulations (SNR). This measure was among the first to assess acculturative stress among an Iranian diaspora population and may be useful in future studies.